EFFECTIVE MICROFERTILIZER POLY-FEED 19-19-19 + 1MgO + ME OF THE COMPANY "HAIFA-CHEMICALS LTD." FOR FOLIAR FERTILIZATION OF CEREALS AND SPRING RAPE - S. M. Sirota; E. G. Kozar; M. M. Tareeva; Ronen Yoav; A. Kuprianov; I. M. Ibragimov; R. R. Khusainov (Овощи России, 2018)
One of the highly effective measures to ensure a cost-effective production of agricultural raw materials is the optimization of mineral nutrition of plants throughout the vegetative period of plants. The efficiency of foliar fertilization with the microfertilizers of Poly-Feed 19-19-19 + 1MgO + ME brand of the company "Haifa Chemicals Ltd." was studied on the development and productivity of cereals: winter and spring wheat, spring barley, and spring rapeseed. Production tests were carried out on the basis of the experimental center of LLC "Kazan Agrokhimservis", located in Pestrechinsky district of Tatarstan. It is established that as a result of foliar application of Poly-Feed fertilizer 19-19-19 + 1MgO + ME, the productive characteristics of the studied crops are improved, such as plant height, spike length, grain size, mass of 1000 seeds; the spring wheat yield is increased by 6.8 centners per hectare, winter wheat - by 11.2 centners per hectare, spring barley - by 5.2 centners per hectare, spring wheat rape - by 4.5 centners per hectare, which is significantly higher that for control plants. At the same time, the qualitative characteristics of the grain are improved: in winter and spring wheat in the experimental variant, it corresponded to grade 3, and in control – to grade 4-5. Utilization of fertilizers by Haifa Chemicals Ltd. of the trade mark Poly-Feed 19-19-19 + 1MgO + ME can be recommended for two-fold foliar application of cereals: winter wheat, spring wheat and spring barley in the tillering phase and in the spike phase, spring rape - in seedlings-rosette and after flowering phase. The recommended dose is 5 kg / ha.